PIODERMA GANGRENOSUM MULTIPEL DAN BERULANG (PERDOSKI, 2022)
Pyoderma gangrenosum is a rare, non-infectious inflammatory skin disease. Diagnosis and treatment are challenging since there are no specific diagnostic criteria or gold standard therapy. The case of a 73 years old man, consulted by surgery department with painful and rapidly progressive necrotic ulcer on his left lower limb and right arm. The initial diagnosis was bacterial ulcer, he underwent debridement and received antibiotics. In the few days, his wound had worsened with enhanced in size and extremely painful. Histological examination showed a dense dermal infiltrate of neutrophil (predominant), lymphocyte, and plasma cell; conformable to pyoderma gangrenosum. Injection of methylprednisolone 31.25 mg / day and mometasone furoate cream 0.1% was given. Clinical improvement was noted in 2 weeks after therapy. Two years later, he developed typical necrotic ulcer on right limb. Pyoderma gangrenosum must be considered in any patient with painful and rapidly progressive ulcer that do not respond to broad-spectrum antibiotics. The histological findings can rule out the other causes of cutaneous ulcer. Suppression of inflammatory process is the main goal in therapy. The delay in identify, inappropriate treatment, and recurrence of the disease remain an issue.